Survey of breast cancer mammography screening behaviors in Eastern Taiwan based on a health belief model - Wenli Wang; Sheng‐Der Hsu; Jen‐Hung Wang; Li‐Chuan Huang; Wen‐Lin Hsu (2014)
Abstract Breast cancer is the main form of cancer affecting women and the fourth most common cause of cancer mortality in women. The aim of this study was to explore regular mammography screening in Hualien women and to identify the factors that influence its uptake based on a health belief model. This cross‐sectional study was performed between July 2012 and December 2012. A total of 776 women aged 45–69 years were enrolled in the study. The results of crude and adjusted analyses showed that there were significant differences in the prevalence of regular mammography screening, which were related to different age groups, residence areas, educational levels, hormone replacement therapy status, and history of breast cancer. Women in the older age groups, with a higher educational level, in receipt of hormone replacement therapy, and with a personal history of breast cancer had significantly higher odds ratios for regular mammography screening (2.75, 1.68, 1.75, and 1.98, respectively; all p < 0.05).